Harnessing antimicrobial peptide-coupled photosensitizer to combat drug-resistant biofilm infections through enhanced photodynamic therapy - Duoyang Fan; Xiaohui Liu; Yueming Ren; Ziheng Luo; Yanbing Li; Jie Dong; Seraphine V. Wegner; Fei Chen; Wenbin Zeng (Elsevier, 2024)
Bacterial biofilm-associated infection was one of the most serious threats to human health. However, effective drugs for drug-resistance bacteria or biofilms remain rarely reported. Here, we propose an innovative strategy to develop a multifunctional antimicrobial agent with broad-spectrum antibacterial activity by coupling photosensitizers (PSs) with antimicrobial peptides (AMPs). This strategy capitalizes on the ability of PSs to generate reactive oxygen species (ROS) and the membrane-targeting property of AMPs (KRWWKWIRW, a peptide screened by an artificial neural network), synergistically enhancing the antimicrobial activity. In addition, unlike conventional aggregation-caused quenching (ACQ) photosensitizers, aggregation-induced emission (AIE) PSs show stronger fluorescence emission in the aggregated state to help visualize the antibacterial mechanism. In vitro antibacterial experiments demonstrated the excellent killing effects of the developed agent against both Gram-positive (G+) and Gram-negative (G-) bacteria. The bacterial-aggregations induced ability enhanced the photoactivatable antibacterial activity against G- bacteria. Notably, it exhibited a significant effect on destroying MRSA biofilms. Moreover, it also showed remarkable efficacy in treating wound infections in mice in vivo. This multifunctional antimicrobial agent holds significant potential in addressing the challenges posed by bacterial biofilm-associated infections and drug-resistant bacteria.